2014
DOI: 10.1016/j.cell.2014.07.024
|View full text |Cite
|
Sign up to set email alerts
|

An Evolutionarily Conserved Prion-like Element Converts Wild Fungi from Metabolic Specialists to Generalists

Abstract: SUMMARY [GAR+] is a protein-based element of inheritance that allows yeast (Saccharomyces cerevisiae) to circumvent a normal hallmark of their biology: extreme metabolic specialization for glucose fermentation. When glucose is present, even in trace quantities, yeast will not use other carbon sources. [GAR+] allows cells to circumvent this “glucose repression.” [GAR+] is induced in yeast by a factor secreted by bacteria inhabiting their environment. We report that the de novo rates of [GAR+] appearance correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
127
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(128 citation statements)
references
References 59 publications
1
127
0
Order By: Relevance
“…Instead it can be heritably eliminated with transient inhibition of Hsp70, such as by expressing a dominant negative variant (Ssa1-K69M – hereafter Hsp70 DN ) (Brown and Lindquist, 2009; Jarosz et al, 2014b). We transformed strains harboring the remaining 35 Hsp104-independent states with a plasmid that constitutively expressed Hsp70 DN , picked multiple transformants, and propagated them three times.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead it can be heritably eliminated with transient inhibition of Hsp70, such as by expressing a dominant negative variant (Ssa1-K69M – hereafter Hsp70 DN ) (Brown and Lindquist, 2009; Jarosz et al, 2014b). We transformed strains harboring the remaining 35 Hsp104-independent states with a plasmid that constitutively expressed Hsp70 DN , picked multiple transformants, and propagated them three times.…”
Section: Resultsmentioning
confidence: 99%
“…Many have argued that most prions represent pathological states (McGlinchey et al, 2011; Nakayashiki et al, 2005). Others have suggested that fungal prions could serve as sophisticated bet-hedging devices that are beneficial in stressful environments (Griswold and Masel, 2009; Halfmann et al, 2012; Jarosz et al, 2014b; True and Lindquist, 2000). Most phenotypic states we identified were benign in rich medium and beneficial in the conditions we used to isolate them.…”
Section: Resultsmentioning
confidence: 99%
“…2). Recent identification of new functional prion-like proteins in various organisms, including human, supports the idea that nonpathogenic prions may perform a wide range of biologically meaningful roles (Coustou et al 1997;Eaglestone et al 1999;True and Lindquist 2000;Ishimaru et al 2003;True et al 2004;Hou et al 2011;Jarosz et al 2014).…”
mentioning
confidence: 95%
“…Indeed, Jarosz et al (2014b) report the existence of genetic mimics of [GAR + ] in several wild strains isolated from soils, and as expected, the defining genetic features of prion-based inheritance are missing in this group. However, this metastable existence is a characteristic of all yeast prions and, in some cases, may provide the host organism with advantageous bet-hedging functions (Halfman and Lindquist, 2010).…”
mentioning
confidence: 87%
“…The resulting bacterial spoilage of the highly valued byproduct of yeast metabolism is typically assumed to be a consequence of the failure of the yeast to produce enough ethanol to give it a growth advantage over the bacteria also found in grape must. Now, two papers in this issue from the Lindquist and Bisson laboratories (Jarosz et al, 2014a(Jarosz et al, , 2014b indicate that, in fact, the ''spoiling'' bacteria trigger, rather than passively capitalize on, the arrest in yeast fermentation by secreting a yet-tobe identified chemical messenger that induces the appearance in the wine yeast of a protein-based epigenetic determinant called [GAR + ] (Figure 1). This chemical dialog with the bacteria is not limited to wine yeasts either but is observed with multiple fruit yeasts and brewing yeasts.…”
mentioning
confidence: 97%